Regional Policy of Uzbekistan: Priorities and the Principles of Implementation (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article substantiates methodological approaches to the development of regional policy, as well as priorities and principles of its implementation. The main objectives, structure and content of the regional policy are formulated. The prerequisites for the economic development of regions that affect their competitiveness are identified, and long-term and medium-term priorities of regional policy are substantiated.